The Impact of Antibiotics on the Development of Colorectal Cancer – A Review of Current Insights and Directions for Future Research - Zagórski, Karol; Kozik, Mateusz; Skalska-Dziobek, Nina; Małagocka, Weronika; Chybowska, Karolina; Naruszewicz, Maria; Cetnarowski, Przemysław (Quality in Sport, 2025)
Introduction and purpose: Colorectal cancer (CRC) is one of the most common neoplasms in the world. In Poland, CRC has a third place in incidence. There are numerous well-established risk factors for CRC, such as a western diet, low physical activity, alcohol consumption, and cigarettes smoking. Currently, the role of the colonic microbiome and the overuse of antibiotics is also highlighted in the pathogenesis of CRC. This review aims to assess the impact of antibiotic use on CRC risk, clinical characteristics, and pathological features. Material and methods: A comprehensive literature search was conducted through the following databases: PubMed, Cochrane Library, Embase, and Google Scholar. Systematic reviews, meta-analyses, clinical trials and observational studies were included if they were relevant and provided data on the influence of antibiotics on CRC. State of knowledge: This review identified several key systematic reviews with meta-analyses of observational studies indicating that antibiotics have an impact on the onset, time of development, and localisation of CRC. The classes and spectrum of antibiotics were found to differ in the risk of occurrence of CRC. Summary: Recently, great progress has been made in understanding a variety of antibiotics-microbiota-cancer interactions. However, further research is needed to deepen our knowledge about the contribution of antibiotic use to CRC. Clinicians should carefully consider the benefits and risks of prescribing antibiotics, including possible long-term adverse events such as cancer onset.